1987
DOI: 10.1172/jci113013
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cholesterol homeostasis in man. Response to changes in dietary fat quality and cholesterol quantity.

Abstract: Studies were carried out to examine the effects of dietary fat and cholesterol on cholesterol homeostasis in man. 75 12-wk studies were carried out during intake of 35% of calories as either saturated or polyunsaturated fat, first low and then high in dietary cholesterol. Dietary fat and cholesterol intakes, plasma lipid and lipoprotein levels, cholesterol absorption and sterol synthesis in isolated blood mononuclear leukocytes were measured during each diet period. In 69% of the studies the subjects compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
4

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(99 citation statements)
references
References 77 publications
2
91
0
4
Order By: Relevance
“…Other studies in free-living subjects, including our previous study, 13 ' 24 -28 failed to demonstrate significant rises in plasma cholesterol with supplements of 250 to 750 mg of cholesterol, although between 21% to 40% of subjects experienced at least a 5% rise. In the present study, half of all subjects experienced a rise of 5% or more in plasma cholesterol with dietary cholesterol.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Other studies in free-living subjects, including our previous study, 13 ' 24 -28 failed to demonstrate significant rises in plasma cholesterol with supplements of 250 to 750 mg of cholesterol, although between 21% to 40% of subjects experienced at least a 5% rise. In the present study, half of all subjects experienced a rise of 5% or more in plasma cholesterol with dietary cholesterol.…”
Section: Discussionmentioning
confidence: 58%
“…9 -13 McNamara et al 13 in an extensive trial of free-living subjects, found that 70% of people could effectively compensate for an increase in dietary cholesterol by down-regulating cholesterol synthesis. A similar proportion of metabolic "compensators" had earlier been reported by Nestel and Poyser.…”
mentioning
confidence: 99%
“…The concept of respondersanonresponders to hypercholesterolemic diets is not new (Ginsberg et al, 1981;McNamara et al, 1987;Glatz et al, 1993). According to Glatz et al (1993) variations in response may be partly random in nature and partly due to metabolic differences among subjects.…”
Section: Effects On Serum Lipoprotein Concentrationsmentioning
confidence: 99%
“…However, a consistent finding from study after study was the high degree of variability in plasma cholesterol responses to dietary cholesterol challenges between patients (24) . In order to explain this variability, and its significance in the dietary cholesterol -heart disease question, it is necessary to consider the inter-individual differences in cholesterol metabolism.…”
Section: Clinical Interventionsmentioning
confidence: 70%